CONCEPT MAPPING: A WAY FOR INVESTIGATING STUDENTS’ MATHEMATICAL UNDERSTANDING - Rizky Oktaviana Eko Putri (Fakultas Ilmu Tarbiyah dan Keguruan (FITK) UIN Siber Syekh Nurjati Cirebon, 2021)
AbstractUnderstanding the concept is one of the main goals in learning mathematics. Teachers as the main pillar in the implementation of learning can use various ways and methods to analyze the extent to which students understand the mathematical concepts being taught. One way that can be used by teachers to observe students' understanding is through a concept map. This study was a qualitative study with the purpose of describing students' understanding on mathematical concepts by using a concept map. The subjects of this study were three students who were selected based on differences in mathematical ability. Students were asked to develop a concept map according to their understanding of the material on mathematical functions. The results show that concept maps can show the level of students' understanding on mathematical concepts based on the number of relationships formed (map complexity). Students with high mathematical abilities can form a fairly complex concept map by showing the relationship of each given concept. On the other hand, students with low mathematical abilities have not been able to show the relationship between the concepts given yet. Keywords: Understanding, Mathematical Concepts, Concept Maps